Stability and stabilization of infinite dimensional systems with applications - Luo, Zheng-Hua; Guo, Bao-Zhu; Morgul, Omer (London: Springer, 1999)
This book reports on recent achievements in stability and feedback stabilization of infinite systems. Various control methods such as sensor feedback control and dynamic boundary control are applied to stabilize the equations.Many new theorems and methods are included in the book.